Religious culture and rural car ownership. (May 2021) - Newmark, Gregory L.; Rearick, Emma L.
Abstract: Transportation policy generally restricts the predictors of car ownership to socio-economic variables without consideration of cultural factors. However, culture – the ideas, norms, and objects that a society shares – affects consumption decisions. Excluding this cultural context may limit consideration of potentially successful policy interventions. The research presented here statistically tests the impact of religious culture on rural car ownership in the United States by incorporating religious adherence rates into statistical models of countywide motorization rates. This research explores whether religious affiliation is a statistically significant predictor of car ownership and whether the addition of those religious variables results in a statistically significant improvement in model fit. The findings suggest that religious affiliation, expressed as countywide adherence rates, is a statistically significant predictor of car ownership and that its inclusion improves model fit; however, while statistically significant, that improvement in model fit is quite small. This research concludes that considering culture is a valuable direction for targeting car consumption policies aimed at curbing climate change. This research also demonstrates the need for additional exploration using disaggregated cultural data to better understand the import of this approach to policy development.